Effect of the structure of gallic acid and its derivatives on their interaction with plant ferritin. (15th December 2016) - Wang, Qunqun; Zhou, Kai; Ning, Yong; Zhao, Guanghua
Highlights: The interaction of gallic acid and its derivatives with ferritin is structure-dependent. These phenolic acids with three HO groups are prerequisite for the interaction. Gallic acid, methyl gallate and propylgallate can bind to ferritin. Such binding can protect ferritin from degradation by pepsin. Abstract: Gallic acid and its derivatives co-exist with protein components in foodstuffs, but there is few report on their interaction with proteins. On the other hand, plant ferritin represents not only a novel class of iron supplement, but also a new nanocarrier for encapsulation of bioactive nutrients. However, plant ferritin is easy to be degraded by pepsin in the stomach, thereby limiting its application. Herein, we investigated the interaction of gallic acid and its derivatives with recombinant soybean seed H-2 ferritin (rH-2). We found that these phenolic acids interacted with rH-2 in a structure-dependent manner; namely, gallic acid (GA), methyl gallate (MEGA) and propyl gallate (PG) having three HO groups can bind to rH-2, while their analogues with two HO groups cannot. Consequently, such binding largely inhibited ferritin degradation by pepsin. These findings advance our understanding of the relationship between the structure and function of phenolic acids.